FLAVONOLIGNANS FOR TREATMENT OF AUTOIMMUNE INFLAMMATORY DISEASES - LIU LIANG; ZHOU HUA; XIE YING (2018)
A method for reducing abnormalities in lipid metabolism and for reducing inflammation in a subject suffering from an autoimmune inflammatory disease accompanied by abnormalities in lipid metabolism includes administering an effective amount of a flavonolignan to the subject. The subject may additionally suffer from a liver disease, obesity, hypertension, diabetes mellitus or a metabolic syndrome.Further provided is a method for reducing the risk of a cardiovascular disease in a subject suffering from an autoimmune inflammatory disease accompanied by abnormalities in lipid metabolism and a method for reducing hepatic abnormalities and reducing inflammation in a subject suffering from an autoimmune inflammatory disease accompanied by hepatic abnormalities. Still further provided is a methodfor reducing liver damages associated with the treatment of rheumatoid arthritis with a disease-modifying antirheumatic drug or a non-steroidal anti-inflammatory drug. 黄酮木脂素在制备用于减少受试者的脂质代谢异常和减少炎症的药物的应用，其中所述受试者患有伴随着脂质代谢异常的自身免疫